2022
DOI: 10.1155/2022/6109040
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Evaluation of Azadirachta indica (Neem) Chip and Soft Tissue Diode Lasers as a Supplement to Phase I Periodontal Therapy in Localized Chronic Moderate Periodontitis: A Randomized Controlled Clinical Trial

Abstract: Introduction. The current trial aimed to assess and compare the efficacy of neem chip and diode laser as a local drug delivery (LDD) agent as a supplement to phase I periodontal therapy in treatment of localized chronic moderate periodontitis. Materials and Methodology. Fourteen systemically healthy participants with 4–6 mm deep periodontal pockets at least in three quadrants (with no alveolar bony defect amenable to respective or regenerative osseous surgery, as seen in orthopantomograph) were selected for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…However, residual pockets after non-surgical therapy may require surgical intervention or tailored recall protocols to address lingering issues [31]. Therefore, different approaches have been proposed to improve the non-surgical periodontal treatment [17,24,32] and to achieve the closure of pockets deeper than 5 mm. One of the most interesting novel techniques is the application of PRF during SRP therapy [17], which likely contributes more than SRP alone.…”
Section: Discussionmentioning
confidence: 99%
“…However, residual pockets after non-surgical therapy may require surgical intervention or tailored recall protocols to address lingering issues [31]. Therefore, different approaches have been proposed to improve the non-surgical periodontal treatment [17,24,32] and to achieve the closure of pockets deeper than 5 mm. One of the most interesting novel techniques is the application of PRF during SRP therapy [17], which likely contributes more than SRP alone.…”
Section: Discussionmentioning
confidence: 99%
“…The acetone extracts of neem were more effective at inhibiting bacterial growth compared to aqueous extracts, which indicates the influence of solvents against bacteria [ 25 ]. Neem chips have been used in addition to scaling, and root planing demonstrated better results in both clinical and microbiological parameters [ 26 ]. Moreover, a clinical trial suggested that neem chips showed benefits in the treatment of periodontitis [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, thick and flat biotypes with thicker gingiva and higher width of the keratinized gingiva are more commonly seen in dentition with wider and shorter crowns and higher interproximal contact areas [ 2 , 3 ]. Gingival thickness is an important component of gingival biotypes and plays a considerable role in the outcome of regenerative periodontal and implant treatments [ 4 , 5 , 6 , 7 ]. In addition to periodontal and implant procedures, gingival thickness also potentially affects the results of orthodontic and restorative treatments [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%